The Effect of Coffee Shop Atmosphere, Lifestyle, and Service Quality on Consumer Purchasing Decisions at Warkop Bening UPN - Andika Firdaus; Rusdi Hidayat Nugroho (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of coffee shop atmosphere, lifestyle, and service quality on consumer purchasing decisions at Warkop Bening UPN. The research applies a quantitative approach using multiple linear regression analysis, with data collected through questionnaires distributed to consumers selected using purposive sampling techniques. The results indicate that coffee shop atmosphere and lifestyle have a positive and significant effect on purchasing decisions, while service quality does not have a significant effect. The regression analysis shows that coffee shop atmosphere is the most dominant variable influencing purchasing decisions, followed by lifestyle. Meanwhile, service quality is perceived as a basic requirement that does not significantly drive consumer decision-making. Furthermore, the coefficient of determination (Adjusted R²) is 0.498, indicating that 49.8% of purchasing decisions are explained by the independent variables, while the remaining 50.2% are influenced by other factors outside the model. The F-test results also confirm that all variables simultaneously have a significant effect on purchasing decisions. These findings highlight the importance of experiential and psychological factors in influencing consumer behavior, particularly among student consumers. This study provides practical implications for coffee shop managers to improve environmental quality and align business strategies with evolving consumer lifestyles.